Hypomethylation of the LncRNA H19 promoter accelerates osteogenic differentiation of vascular smooth muscle cells by activating the Erk1/2 pathways - Taoxia Wang; Meijuan Cheng; Jingjing Jin; Yaling Bai; Dongxue Zhang; Shenglei Zhang; Jinsheng Xu (Journal of International Medical Research)
Objective Vascular calcification is a common chronic kidney disease complication. This study aimed to investigate the function of long non-coding RNA (LncRNA) H19 in vascular calcification to explore new therapeutic strategies. Methods We induced osteogenic differentiation and calcification of vascular smooth muscle cells (VSMCs) using β-glycerophosphate. Then, we detected the LncRNA H19 promoter methylation status and Erk1/2 pathways using methylation-specific polymerase chain reaction and western blotting, respectively. Results Compared with the control group, high phosphorus levels induced VSMC calcification, accompanied by increases in LncRNA H19 and the osteogenic marker Runx2 and reduction of the contractile phenotype marker SM22a. LncRNA H19 knockdown inhibited osteogenic differentiation and calcification of VSMCs. However, the suppressed role of VSMC calcification caused by shRNA H19 was partially reversed by simultaneous activation of the Erk1/2 pathways. Mechanically, we found that the methylation rate of CpG islands in the LncRNA H19 promoter region was significantly lower in the high-phosphorus group, and the hypomethylation state elevated LncRNA H19 levels, which in turn regulated phosphorylated Erk1/2 expression. Conclusions LncRNA H19 promoted osteogenic differentiation and calcification of VSMCs by regulating the Erk1/2 pathways. Additionally, hypomethylation of LncRNA H19 promoter CpG islands upregulated LncRNA H19 levels and subsequently activated Erk1/2 phosphorylation.